Urban poverty and life well-being among lower-ranking police officers: an exploratory study in Kuala Lumpur - Ramzi Ahad; Khauthar Ismail; Zurina Mohd Radzi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The issue of urban poverty and its impact on the well-being of lower-ranking government servants has required attention from related agencies. Due to their job prospects and secure monthly salary, they can easily be overlooked as a group which might be affected by urban poverty. The main objective of this paper is to explore the impact of urban poverty on lower-ranking police officers in an urban area. Eleven semi-structured in-depth interviews were conducted among police officers in Kuala Lumpur. All informants were recruited through random sampling based on their specific rank, salary range and stationed location. The acquired data were analysed through thematic analysis: wealth, education and health. The results suggest that all informants were relatively distressed by urban poverty, especially for monthly survival. The imbalance between salary and high living costs in the city significantly impacted their food security, financial savings, children's education and health scheme planning. Theoretically, the research substantiates poverty as a multidimensional concept rather than a single dimension. In addition, the finding on the non-financial dimension of poverty can be used as guidelines in the government's future planning and initiatives to curb urban poverty among lower-ranking government officials.